Science educational game: Increase procedural knowledge? - Dimas Wahyu Indrata; Arum Adita; Muvida Nofiana (Universitas Ahmad Dahlan, 2020)
Developing educational game as an alternative of science learning media in SMP Negeri 1 Sokaraja. The purpose of this study was to determine the level of feasibility of science education games and to determine the effect of games on students' procedural knowledge. The designed educational game contained testing procedure of food substances on the materials of digestive system. The research was taken place in SMP Negeri 1 Sokaraja. The sample in this study were 33 eight grade students. The method used was ADDIE Analysis; Design Development and Implementation, and Evaluation. The instruments used were questionnaires, pre-test questions, and post-test questions. Quantitative analysis techniques were used for data analysis. The results of the game feasibility were determined through validation activities by material experts, media experts, teachers and students. The feasibility of the game by material experts indicated a percentage of 90% with a good category, media experts proved a percentage of 72.85% with adequate categories, science teachers showed a percentage of 95.68% with a good category and the eligibility by students confirmed a percentage of 79.02% with a good category. N-Gain Test Value of 0.179 meant that the effect of games as a science learning media was in low category.